A Mathematical Model for the Instigation and Transmission of Biological and Neural Signals in Response to Acupuncture (Communications in Computational Physics, 2020)
Acupuncture has been in clinical practice in China for thousands of yearsand its analgesia effect is worldwide accepted. However, the mechanism of acupunctureeffect is not well understood. The study focuses on signaling pathways inducedby acupuncture, analyzes the cooperative action of the acupoints' structure and theassociated chemical mediators during acupuncture, establishes a mathematical modelclarifying the roadmap of electroneurographic signal startup and transmission mechanisminduced by acupuncture, quantitatively analyzing the response in acupoints toacupuncture. These work contributes to reveal the activation and transmission mechanismof neural signals induced by acupuncture from systems biology perspective,lays the foundation for the integration of acupuncture theory and modern science andfurther guides the clinical treatment and experimental research of acupuncture.